Relationship between electrocardiographic findings and Cardiac Magnetic Resonance phenotypes in patients with Hypertrophic Cardiomyopathy. (June 2016) - Fronza, Matteo; Raineri, Claudia; Valentini, Adele; Bassi, Emilio Maria; Scelsi, Laura; Buscemi, Maria Laura; Turco, Annalisa; Castelli, Grazia; Ghio, Stefano; Visconti, Luigi Oltrona
Abstract: Background: Q waves and negative T waves are common electrocardiographic (ECG) abnormalities in patients with Hypertrophic Cardiomyopathy (HCM). Several studies correlated ECG findings with presence and extent of fibrosis and hypertrophy; however, their significance remains incompletely clarified. Our study aimed to explain the mechanism behind Q and negative T waves by comparing their positions on a 12-lead ECG with phenotypes observed at Late Gadolinium Enhancement (LGE) Cardiac Magnetic Resonance (CMR). Methods: 12-lead ECG and LGE-CMR were performed in 88 consecutive patients with HCM (42 SD 16 years, 65 males). Using Delta Thickness ratio (DT ratio), and "global" and "parietal" LGE at CMR, the extent and distribution of myocardial hypertrophy and fibrosis were studied in correlation with ECG abnormalities. Results: Q waves in different leads were not associated with "parietal" LGE score. Lateral Q waves correlated with an increased DT ratio Inferior Septum/Lateral wall ( p = 0.01). A similar correlation between inferior Q waves and an increased DT Ratio Anterior wall/Inferior wall was of borderline statistical significance ( p = 0.06). As expected, ECG signs of LV hypertrophy related to a raised Left Ventricular Mass Index (LVMI) ( p < 0.0001) and mean wall thickness ( p = 0.01). Depolarization disturbances, including negative T waves in lateral ( p = 0.044) and anterior ( p = 0.031) leads correlated with "parietal" LGE scores while QT dispersion ( p = 0.0001) was associated with "global" LGE score. Conclusion: In HCM patients, Q waves are generated by asymmetric hypertrophy rather than by myocardial fibrosis, while negative T waves result from local LGE distribution at CMR.